2013
DOI: 10.1093/epirev/mxs004
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Relationship Between Physical Function and Cognition in Longitudinal Aging Cohorts

Abstract: On average, older people remember less and walk more slowly than do younger persons. Some researchers argue that this is due in part to a common biologic process underlying age-related declines in both physical and cognitive functioning. Only recently have longitudinal data become available for analyzing this claim. We conducted a systematic review of English-language research published between 2000 and 2011 to evaluate the relations between rates of change in physical and cognitive functioning in older cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
328
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(363 citation statements)
references
References 76 publications
24
328
2
9
Order By: Relevance
“…Their respective relationships with the long-term persistence of health-related behaviors over time are less well understood, particularly in the context of aging. Older age is a time period in life when maintaining healthy lifestyle behaviors can become particularly challenging due to changing life circumstances including increasing risks of physical and cognitive impairments [23]. At the same time, healthy behaviors become increasingly important in later life for the maintenance of quality of life and well-being [24].…”
Section: Introductionmentioning
confidence: 99%
“…Their respective relationships with the long-term persistence of health-related behaviors over time are less well understood, particularly in the context of aging. Older age is a time period in life when maintaining healthy lifestyle behaviors can become particularly challenging due to changing life circumstances including increasing risks of physical and cognitive impairments [23]. At the same time, healthy behaviors become increasingly important in later life for the maintenance of quality of life and well-being [24].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review reported standardized b regression coefficients comprised between 0.05 and 0.15 34 ; the authors concluded that the observed associations were not sufficiently strong or consistent to provide conclusive evidence for common causes. 34 Cognition appears not to have a major role in the education-WS association: in our study, MMSE explained 15% of the association; using alternative tests (Isaac Test, Benton Visual Retention Test, Trail Making Test) yielded similar conclusions (data not shown). Finally, because childhood and adult SES are independently associated with slower WS in old age, 35 parental education was used as a surrogate for childhood SES and attenuated the education-WS association by approximately 12%.…”
mentioning
confidence: 99%
“…In their systematic review, Clouston et al 33) reported finding an association between grip strength and cognitive function, with grip strength predicting the development of Alzheimer's disease 34) . However, they concluded that the associations between grip strength and cognitive function were not sufficiently strong to provide conclusive evidence for "common cause" aging.…”
Section: Validity As a Predictor Of Geriatric Concernsmentioning
confidence: 99%